Corneal Endothelial Cells Have an Absolute Requirement for Cysteine for Survival. Issue 8 (August 2017) - Okumura, Naoki; Inoue, Ryota; Kakutani, Kazuya; Nakahara, Makiko; Kinoshita, Shigeru; Hamuro, Junji; Koizumi, Noriko
Abstract : Purpose: The aim of this study was to evaluate which amino acid(s) among the 20 standard protein amino acids is indispensable for the survival of cultured human corneal endothelial cells (HCECs). Methods: HCECs were cultured in amino acid screening media that were missing 1 specific amino acid, and cell growth was evaluated. After this first selection, we conducted a further evaluation of cell growth in response to the addition of 4 amino acids (cysteine, methionine, valine, and arginine) to amino acid-free culture media. We then evaluated the antioxidant effect of cysteine compared with other antioxidants in terms of apoptosis of HCECs, rabbit corneal endothelial cell (CECs), monkey CECs, and ex vivo human donor corneas. Results: Culture in an amino acid-free Dulbecco Modified Eagle Medium (DMEM) decreased the cell numbers to 11.0% when compared with culture in normal DMEM. Removal of cysteine, methionine, valine, or arginine from DMEM significantly suppressed cell numbers (27.7%, 61.4%, 75.5%, and 60.6%, respectively) ( P < 0.01), whereas removal of other amino acids did not significantly decrease cell numbers. A lack of cysteine induced apoptosis, but addition of antioxidants reversed this. Removal of cysteine induced in vitro apoptosis in HCECs, rabbit CECs, monkey CECs, and ex vivo human donor corneas, whereas the presence of cysteine almost completely suppressed this apoptosis. Conclusions: Cysteine seems to be an indispensable amino acid for HCEC growth and survival. Its necessity might reflect a high requirement for antioxidants to protect HCECs from oxidative stress, as HCECs have high aerobic metabolic activity.